REPRESENTASI PESAN MORAL PADA FILM “ANAK GARUDA” (Analisis Semiotika John Fiske) - Hendrawan, Bagus; Hudoyo, Sapto (JURNAL PAKARENA, 2024)
Anak Garuda is a fictional movie that contains many moral values. The purpose of this research is to describe the representation of moral messages in Anak Garuda by using John Fiske's Semiotic analysis through three levels of approach, namely reality, representation, and ideology. The analysis method used is qualitative research based on the stages of Jane Stokes' Semiotic analysis. The results of this study are moral values towards God Almighty, moral values towards oneself, and moral values towards relationships with others.